IMPROVING THE STUDENTS’ READING COMPREHENSION THROUGH CAROUSEL BRAINSTORM STRATEGY - Burhanuddin, Wildhan (Fakultas Keguruan dan Ilmu Pendidikan, 2015)
This research aimed to explain about how is the Improving the Students’ Reading Comprehension Through Carousel Brainstorm Strategy At The Second Students Of MA (Madrasah Aliyah) Al-Hikma Kab. Mamuju Utara. The problem statement of the research were how is the improvement of the students’ literal comprehension through Carousel Brainstorm Strategy. The researcher used a Classroom Action Research (CAR). The researcher conducted two cycles, where each cycle consisted of four meetings. It employed descriptive test as instrument. A number of subjects of the research were 47 students in the second class of MA (Madrasah Aliyah) Al-Hikma. The researcher took real data from the school to know the students’ reading comprehension. In term of collecting data the researcher used category proposed by Gay (1981) to grade students’ achievement in reading comprehension during the research sessions. The research findings indicated that Carousel Brainstorm Strategy can improve of the students’ reading comprehension where the means score of D-Test (51.1%) and after evaluation in cycles I and II, the means scores improvement from (68.1%) in the first cycle and (78.2%) in the second cycle. Thus, the improvement of the student’s reading comprehension from D-Test to cycle I (33.26%) and cycle I to cycle II (14.83%) and from D-Test to cycle II  (53.03%) While the standard target achievement KKM 75. Based on the score in cycle II the score categorized as Good. It can be stated that  the students’ reading comprehension at the second grade students of  MA (Madrasah  Aliyah) Al-Hikma was a low level before the test in the first cycle and the position of reading comprehension moved into a high level after the test in the second cycle.